2012
DOI: 10.1007/978-3-642-34191-5_16
|View full text |Cite
|
Sign up to set email alerts
|

Compact Grid Representation of Graphs

Abstract: Abstract.A graph G is said to be grid locatable if it admits a representation such that vertices are mapped to grid points and edges to line segments that avoid grid points but the extremes. Additionally G is said to be properly embeddable in the grid if it is grid locatable and the segments representing edges do not cross each other. We study the area needed to obtain those representations for some graph families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…As a consequence we obtain that drawing/locating of graphs on a bounded number of columns is a difficult task answering the open question in [2]. This problem was already partially solved, as Chappell, Gimbel and Hartman [3] proved that determining whether G can be colored with at least two path colors is NPcomplete.…”
Section: Corollarymentioning
confidence: 93%
See 2 more Smart Citations
“…As a consequence we obtain that drawing/locating of graphs on a bounded number of columns is a difficult task answering the open question in [2]. This problem was already partially solved, as Chappell, Gimbel and Hartman [3] proved that determining whether G can be colored with at least two path colors is NPcomplete.…”
Section: Corollarymentioning
confidence: 93%
“…al. [2] showed that every outerplanar graph can be drawn (and located) on two columns. In the same paper there is an example of a planar graph which is not (2, 1)-colorable.…”
Section: Corollarymentioning
confidence: 99%
See 1 more Smart Citation
“…, V 2 d such that every induced subgraph G [V i ] is isomorphic to a linear forest. As the basis of the induction we use the proof of a weaker theorem proven in [8].…”
Section: If There Are Two Setsmentioning
confidence: 99%
“…al. [8] showed that every outerplanar graph can be drawn (and located) on two columns. In the same paper there is introduced an example of a planar graph which is not (2, 1)-colorable.…”
Section: Mixed Coloringsmentioning
confidence: 99%